Experimental and Genomic Evaluation of the Oestrogen Degrading Bacterium Rhodococcus equi ATCC13557 - Harthern-Flint, Sarah L.; Dolfing, Jan; Mrozik, Wojciech; Meynet, Paola; Eland, Lucy E.; Sim, Martin; Davenport, Russell J. (Frontiers in Microbiology, 2021)
R. equi ATCC13557 was selected as a model organism to study estrogen degradation based on its previous ability to degrade 17α-ethinylestradiol (EE2). Biodegradation experiments revealed that R. equi ATCC13557 was unable to metabolise EE2. However, it was able to metabolise E2 with the major metabolite being E1 with no further degradation of E1. However, the conversion of E2 into E1 was incomplete, with 11.2% and 50.6% of E2 degraded in mixed (E1-E2-EE2) and E2- only conditions, respectively. Therefore, the metabolic pathway of E2 degradation by R. equi ATCC13557 may have two possible pathways. The genome of Rhodococcus equi ATCC13557 was sequenced, assembled, and mapped for the first time. The genome analysis allowed the identification of genes possibly responsible for the observed biodegradation characteristics of R. equi ATCC13557. Several genes within R. equi ATCC13557 are similar, but not identical in sequence, to those identified within the genomes of other estrogen degrading bacteria, including Pseudomonas putida strain SJTE-1 and Sphingomonas strain KC8. Homologous gene sequences coding for enzymes potentially involved in estrogen degradation, most commonly a cytochrome P450 monooxygenase (oecB), extradiol dioxygenase (oecC), and 17β- hydroxysteroid dehydrogenase (oecA), were identified within the genome of R. equi ATCC13557. These searches also revealed a gene cluster potentially coding for enzymes involved in steroid/estrogen degradation; 3-carboxyethylcatechol 2,3-dioxygenase, 2-hydroxymuconic semialdehyde hydrolase, 3-alpha-(or 20-beta)-hydroxysteroid dehydrogenase, 3-(3-hydroxy-phenyl)propionate hydroxylase, cytochrome P450 monooxygenase, and 3-oxosteroid 1-dehydrogenase. Further, the searches revealed steroid hormone metabolism gene clusters from the 9, 10-seco pathway, therefore R. equi ATCC13557 also has the potential to metabolise other steroid hormones such as cholesterol.